Axial compressive behavior of middle partially encased composite brace. (June 2023) - Huang, Hua; Chen, Zhen; Ye, Yanxia; Yao, Yifan
Abstract: To prevent the buckling and unbalanced tensile-compressive behavior of steel braces, a middle partially encased composite brace (MPEC) is proposed in this paper. In this composite brace, concrete is encased in the middle section of the H-shaped steel, and stiffeners are welded in the steel section for reinforcement. Axial compressive tests were implemented on four MPEC braces and one comparison specimen with considering the flange thickness, longitudinal reinforcement ratio, stirrup spacing and slenderness. The test results revealed that the failure of all composite braces was due to local buckling of the flange plates and separation from the concrete. The presence of concrete within the steel flange effectively limited the buckling of the H-shaped steel and improved the stiffness and compressive capacity. The compressive capacity of the composite braces was primarily influenced by the sectional dimension of the H-shaped steel, while the contribution of the reinforced concrete was limited. Additionally, a higher longitudinal reinforcement ratio improved the ductility of the composite braces, while larger stirrup spacing reduced both the compressive capacity and ductility. The specimen with large slenderness demonstrated poor mechanical properties and experienced a more abrupt failure. The axial compressive capacity of MPEC braces was calculated based on the critical buckling stress of steel plate and the confinement of concrete in partially encased composite columns (PEC). The calculated results showed good accuracy compared to the experimental data, and thus, the formula proposed in this study can be applied in design applications to predict the axial compressive capacity of MPEC braces. Highlights: Compared to steel brace, MPEC brace exhibits higher initial stiffness and compressive capacity. The main factor affecting the compressive capacity of MPEC brace is the thickness of the flange plate. The reinforced concrete in MPEC brace can effectively prevent the loss of overall stability of H-shaped steel. The formulas proposed in this study can provide a useful reference for practical engineering designs.